Skeleton Maps in Anatomy and Physiology: Student Perceptions - Michelle Yeo; Sarah Hewitt; Joanne Bouma; Sarah Lang (Canadian Journal for the Scholarship of Teaching and Learning)
Heavy content, high volume courses commonly create challenges for undergraduate students. Two such courses at our university are the introductory semesters of anatomy and physiology for first-year nursing students, taught by biology instructors. Despite the vast literature indicating the efficacy of using concept maps as a tool for learning, it is still not commonly implemented in the field. An adaptation called skeleton maps, were developed and implemented to assist student learning. This qualitative SoTL study reports on student perceptions of the learning gains of utilizing these maps, under six themes that fall into behavioural, cognitive, and opinion-based categories. The results of this study indicate a strong evidence base for using concept-map based strategies within similar courses.